Modulation of the solar activity on the connection between the NAO and the tropical pacific SST variability - Huo, Wenjuan; Xiao, Ziniu; Zhao, Liang (Frontiers in Earth Science, 2023)
Previous studies indicated that the North Tropical Atlantic (NTA) SST can serve as a precursor for the El Niño–Southern Oscillation (ENSO) predictability and the connection of NTA-ENSO is modulated by the mid-high latitude atmospheric variability. Despite significant solar footprints being found in the North Atlantic and tropical Pacific separately, their role in the two basins’ connection is still missing. In this study, we systematically examined this point by using observational/reanalysis datasets and outputs of a pair of sensitivity experiments with and without solar forcings (SOL and NOSOL). In observations, DJF-mean NAO-like SLP anomalies have a linear covariation with the subsequent JJA-mean El Niño Modoki-like SST anomalies in the tropical Pacific in the following 1 year. This observed SLP-SST covariation shows up in the high solar activity (HS) subset and disappears in the low solar activity (LS) subset. In the HS years, positive NAO-like SLP anomalies are produced by the stronger solar-UV radiation through a “top-down” mechanism. These atmospheric anomalies can enhance the influence of the NTA on the tropical Pacific SST by triggering significant and more persistent subtropical teleconnections. Here we proposed an indirect possible mechanism that the solar-UV forcing can modulate the tropical Pacific SST variability via its impacts on the atmospheric anomalies over the North Atlantic region. However, based on the same analysis method, we found a different coupled mode of the SLP and SST anomalies in the modeling outputs. The SLP anomalies in the North Atlantic, with a triple pattern (negative SLP anomalies in the Pole and the north tropical Atlantic, positive SLP anomalies in the mid-latitude), have “lead-lag” covariations with the Eastern Pacific El Niño-like SST anomalies in both the SOL and NOSOL. Although the impact of the solar activity is found in the North Atlantic and the tropical Pacific respectively in the SOL, no solar effect is involved in the simulated SLP-SST coupled mode.